2022
DOI: 10.21511/imfi.19(1).2022.04
|View full text |Cite
|
Sign up to set email alerts
|

Value-at-risk (VAR) estimation and backtesting during COVID-19: Empirical analysis based on BRICS and US stock markets

Abstract: Value-at-risk (VaR) is the most common and widely used risk measure that enterprises, particularly major banking corporations and investment bank firms employ in their risk mitigation processes. The purpose of this study is to investigate the value-at-risk (VaR) estimation models and their predictive performance by applying a series of backtesting methods on BRICS (Brazil, Russia, India, China, South Africa) and US stock market indices. The study employs three different VaR estimation models, namely normal (N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Linsmeier and Pearson (1996) also defined VaR as a measure of the downside risk and the chance to lose more than the amounts indicated by the measure is very low, as it depends on the confidence level used to calculate the VaR over a certain period (Berkelaar, 2002). Nevertheless, Shaik and Padmakumari (2022) conclude that using VaR in investment bank firms and significant banking corporations to mitigate risks has shown poor performance when used in periods of crisis. Bali et al (2004) conclude that VaR can seize significant time-series variation in stock returns.…”
Section: Methodsmentioning
confidence: 99%
“…Linsmeier and Pearson (1996) also defined VaR as a measure of the downside risk and the chance to lose more than the amounts indicated by the measure is very low, as it depends on the confidence level used to calculate the VaR over a certain period (Berkelaar, 2002). Nevertheless, Shaik and Padmakumari (2022) conclude that using VaR in investment bank firms and significant banking corporations to mitigate risks has shown poor performance when used in periods of crisis. Bali et al (2004) conclude that VaR can seize significant time-series variation in stock returns.…”
Section: Methodsmentioning
confidence: 99%
“…COVID-19 pandemic has created turbulence in the global financial markets (Salisu et al ., 2020; Singh et al ., 2021; Shaik et al ., 2022). Atri et al .…”
Section: Review Of Literature and Theoretical Frameworkmentioning
confidence: 99%
“…COVID-19 pandemic has created turbulence in the global financial markets (Salisu et al, 2020;Singh et al, 2021;Shaik et al, 2022). Atri et al (2021) found, using the ARDL approach, that the Covid-19 deaths and panic had an adverse effect on crude oil prices but an optimistic effect on gold prices, suggesting gold as a safe haven during pandemic.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It builds upon Christoffersen's ideas [50] and incorporates them into a more powerful metric. TBFI is a likelihood ratio test defined in [51] as:…”
Section: Used Metricsmentioning
confidence: 99%